Pertanggungjawaban Pidana Korporasi Yang Melakukan Tindak Pidana Di Bidang Perikanan (Illegal Fishing) - Kristayudasoeparno, Rionaldo Jehova; Setiabudhi, I Ketut Rai (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020), 2020)
The purpose of this paper is to examine the theoretical foundation or basis used to be able to hold accountable to corporations suspected of having committed criminal acts in the field of fisheries and forms of corporate criminal liability provided for in the Fisheries Law. The research method used in this study is a normative legal research method and the use of the approach used is the statutory approach by making Law Number 31 of 2004 concerning Fisheries as the object of study. The results of the study show that various doctrines or teachings on the justification for imposing criminal liability on corporations include strict liability, vicarious liability, doctrine of identification, and doctrine of delegation. The regulation of corporations as subject to criminal offenses in the field of fisheries (IUU Fishing) is set explicitly in the provisions of Article 101 of the Fisheries Law. The concept of corporate criminal liability contained in the Fisheries Act still adheres to the principle that the management is responsible if the corporation commits a criminal offense. This arrangement has weaknesses because there is the potential for corporations to repeat illegal fishing. The Fisheries Law also does not set boundaries in terms of what criminal acts are committed by corporations. In addition, the concept of criminal liability for corporations that commit criminal acts in the fisheries sector is regulated in the Draft Law on Fisheries.   Key Words: Criminal Liability, Corporations, IUU Fishing.